2015
DOI: 10.1016/j.solmat.2015.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast pump-probe reflectance spectroscopy: Why sodium makes Cu(In,Ga)Se2 solar cells better

Abstract: (O.F.M.) 2 | P a g e TOC graphicCIGS thin-film samples were investigated for the first time using femtosecond pump-probe differential reflection spectroscopy with broadband capabilities and 120-fs temporal resolution.The pump-and-probe beams were focused on ~1.6 m-thick CIGS films. The reflected probe light from the samples was collected and focused on the broadband infrared detector (D) for recording the carrier dynamics of CIGS in real time.3 | P a g e ABSTRACT Although Cu(In,Ga)Se 2 (CIGS) solar cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The morphology of particles is still spherical as that of CdSe QDs (used as a template) after cation exchange, which indicates that the shape and morphology of CdSe particles in the SnSe/CdSe HS system Understanding the carrier cooling and transfer dynamics across the junction of the SnSe/CdSe HS plays a pivotal role in improving the performance of the devices such as solar cells, photodetectors etc. 36,37 The optical absorption spectrum of SnSe NSs presented in Figure 3A,a shows a broad absorption band in the region from 400 to 1600 nm peaking around 700 nm. The band gap of SnSe was calculated using a tauc plot, which is shown in Figure 3A inset.…”
Section: Snmentioning
confidence: 99%
“…The morphology of particles is still spherical as that of CdSe QDs (used as a template) after cation exchange, which indicates that the shape and morphology of CdSe particles in the SnSe/CdSe HS system Understanding the carrier cooling and transfer dynamics across the junction of the SnSe/CdSe HS plays a pivotal role in improving the performance of the devices such as solar cells, photodetectors etc. 36,37 The optical absorption spectrum of SnSe NSs presented in Figure 3A,a shows a broad absorption band in the region from 400 to 1600 nm peaking around 700 nm. The band gap of SnSe was calculated using a tauc plot, which is shown in Figure 3A inset.…”
Section: Snmentioning
confidence: 99%
“…[ 7,9,11,12 ] Other studies showed that the increase in V OC and FF can result from the passivation of non‐radiative recombination centers at grain boundaries (GBs), evidenced by several atom probe tomography studies showing Na accumulation predominantly at GBs compared to grain interiors (GIs). [ 13–20 ] Transient optical studies correlated increased charge carrier lifetime with optimal Na atom incorporation [ 21–23 ] Eid et al utilized ultrafast pump‐probe reflectance spectroscopy to study Ga‐graded CIGSe devices with different thicknesses of NaF (incorporated prior to selenization) and found a 1.5‐fold increase in minority carrier lifetime in samples with higher Na concentrations which was correlated with higher device performance [ 10,21 ] However, owing to the variation in the composition gradient with different Na concentrations in this experiment design, the role of Na atoms could not be clearly identified. Lee et al detected a ≈fivefold prolonged charge carrier lifetime on CIGSe (GGI = 0.14) grown on SLG compared to reference films grown on borosilicate glass, concluding that the addition of Na atoms prohibits the formation of defect states at the CdS/CIGSe junction and hence increases carrier lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…This surface treatment improves the open circuit voltage ( V OC ) and fill factor (FF) of the device. , Depending on the deposition technique, several mechanisms have been proposed for the efficiency enhancement, which can be broadly classified into two categories(a) influence on growth kinetics that leads to different grain sizes, smoother texture, and suppression of defect formation and (b) improvement of electronic properties by removal of deleterious donor states and introduction of acceptor states, which in turn increases the net hole concentration and hence p-type conductivity. ,, In addition, Na is reported to passivate grain boundary defects and reduce minority carrier traps. , However, the exact reason for such efficiency enhancement remains under debate. One of the reasons behind this is the lack of suitable surface-sensitive characterization techniques that can observe charge carrier dynamics in real time, precisely on the surface, as it is well-known that Na is mostly localized onto the surface of CIGSe, rather than in the bulk of the film. ,,,, The structural changes on the surface post Na incorporation can be verified following several microscopic and spectroscopic characterization techniques; however, its effects on modifying the electronic properties of CIGSe have only been inferred from the device measurements or predicted from theoretical calculations. Spectroscopic studies have also been reported to understand the effect of Na on charge carrier dynamics; however, because of the large penetration depth of the laser beam, these studies provide the dynamical information mainly from the bulk of the material rather than the surface. , …”
Section: Introductionmentioning
confidence: 99%
“…12−28 Spectroscopic studies have also been reported to understand the effect of Na on charge carrier dynamics; however, because of the large penetration depth of the laser beam, these studies provide the dynamical information mainly from the bulk of the material rather than the surface. 29,30 Herein, we explore and decipher the impact of Na incorporation on CIGSe NCs thin film by four-dimensional scanning ultrafast electron microscopy (4D S-UEM), which has the unique capability to visualize charge carrier dynamics selectively on material surfaces in real time and space with unprecedented spatial and temporal resolution. 11,31−39 The concept of the experimental technique is depicted in Scheme 1.…”
Section: ■ Introductionmentioning
confidence: 99%